Susceptibility to acute cognitive dysfunction in aged mice is underpinned by reduced white matter integrity and microgliosis - Dáire Healy; Carol Murray; Ciara McAdams; Ruth Power; Pierre-Louis Hollier; Jessica Lambe; Lucas Tortorelli; Ana Belen Lopez-Rodriguez; Colm Cunningham (Communications Biology, 2024)
Abstract Age is a significant but heterogeneous risk factor for acute neuropsychiatric disturbances such as delirium. Neuroinflammation increases with aging but the determinants of underlying risk for acute dysfunction upon systemic inflammation are not clear. We hypothesised that, with advancing age, mice would become progressively more vulnerable to acute cognitive dysfunction and that neuroinflammation and neuronal integrity might predict heterogeneity in such vulnerability. Here we show region-dependent differential expression of microglial transcripts, but a ubiquitously observed primed signature: chronic Clec7a expression and exaggerated Il1b responses to systemic bacterial LPS. Cognitive frailty (vulnerability to acute disruption under acute stressors LPS and double stranded RNA; poly I:C) was increased in aged animals but showed heterogeneity and was significantly correlated with reduced myelin density, synaptic loss and severity of white matter microgliosis. The data indicate that white matter disruption and neuroinflammation may be key substrates of the progressive but heterogeneous risk for delirium in aged individuals.